Simultaneous Occurrence of Tropical Cyclones in the Northern Indian Ocean: Differential Response and Triggering Mechanisms - Roy Chowdhury, Riyanka; Prasanna Kumar, S.; Chakraborty, Arun (Frontiers in Marine Science, 2021)
The northern Indian Ocean, comprising of two marginal seas, the Arabian Sea (AS) and the Bay of Bengal (BoB), is known for the occurrence of tropical cyclones. The simultaneous occurrence of the cyclones Luban in the AS and Titli in the BoB is a rare phenomenon, and, in the present study, we examined their contrasting upper ocean responses and what led to their formation in October 2018. Being a category-2 cyclone, the maximum cooling of sea surface temperature associated with Titli was 1°C higher than that of Luban, a category-1 cyclone. The higher tropical cyclone heat potential in the BoB compared with the AS was one of the reasons why Titli was more intense than Luban. The enhancement of chlorophyll a (Chl-a) and net primary productivity (NPP) by Luban was 2- and 3.7-fold, respectively, while that by Titli was 3- and 5-fold, respectively. Despite this, the magnitudes of both Chl-a and NPP were higher in the AS compared with the BoB. Consistent with physical and biological responses, the CO2 outgassing flux associated with Titli was 12-fold higher in comparison to the pre-cyclone value, while that associated with Luban was 10-fold higher. Unlike the Chl-a and NPP, the magnitude of CO2 flux in the BoB was higher than that in the AS. Although the cyclones Luban and Titli originated simultaneously, their generating mechanisms were quite different. What was common for the genesis of both cyclones was the pre-conditioning of the upper ocean in 2018 by the co-occurrence of El Niño and the positive phase of Indian Ocean dipole along with the cold phase of the Pacific decadal oscillation, all of which worked in tandem and warmed the AS and parts of the BoB. What triggered the genesis of Luban in the AS was the arrival of the Madden–Julian oscillation (MJO) and the mixed Rossby-gravity wave during the first week of October. The genesis of Titli in the BoB was triggered by the eastward propagation of the MJO and the associated enhanced convection from the AS into the region of origin of Titli along with the arrival of the downwelling oceanic Rossby wave.